STUDI RUANG LABORATORIUM BAYI TABUNG UNHAS DALAM PERANCANGAN ARSITEKTUR - Dwiasta R, Andi Yusdi (FORUM BANGUNAN, 2013)
Studies in the architectural design space will make the design work more optimal design and targeted, one way is to pay attention to aspects of the design. Physical aspects and non-physical aspects of becoming an effort to manipulate the architectural space in order to avoid improper assumptions in architectural design. Keywords: studi ruang, perancangan, laboratorium bayi tabung